Conceptual approaches to the social infrastructure concept in economics - Nakipova, G.N.; Spanova , B.K. (BUKETOV BUSINESS REVIEW, 2017)
The paper presents main theoretical and methodological approaches to the «social infrastructure» category, identifies main distinctive features between infrastructure and social infrastructure. Definitions of the social infrastructure functioning theory as an important component of the regional economy providing production and consumption of services and non-material benefits are considered. Social infrastructure notion interpretations are diverse, which is explained by the absence of clearly substantiated principles, criteria of attributing certain industries to it, types of industries or activities. Providing public and non-excludable benefits, social infrastructure is the determining factor for successful socio-economic development and functioning of the region. It was revealed that the conditions for rural social infrastructure are specific due to insufficient budget resources. The analysis showed that rural social infrastructure development promotes and ensures efficient allocation of productive forces and forms of labour relations, including agro-industrial production. Social infrastructure development is becoming one of the most important priorities for economic modernization, since infrastructure services provide the basis for increasing all economy sectors’ efficiency.